Membumikan Operasi Perusahaan Besar di Indonesia: Melalui Pola Kemitraan dengan UKM: Sebuah Alternatif Pemikiran - Prasetyantoko, A.; Parmono, Rachmadi (Universitas Prasetiya Mulya, 2008)
The financial crisis of the 1997 can be considered as an important “wakeup-call” for Indonesian businesses. Before the crisis, business systems were maintained poorly as indicated by widespread of corruption and unfair business practices. Many observers claimed that this kind of business habits became one of important factors that trigger the crisis. Interestingly, unlike big companies related to conglomeration, small and medium enterprises (SMEs) survived during this difficult time. Several factors might be responsible to this phenomenon: flexibility, informality, communality and responsiveness. In post-crisis period, businesses in Indonesia should restructure their systems and behavior by adopting some basic principles of small business while strengthening their corporate governance. Partnership with SMEs is one of the best strategies to do that in this new era.